PENGARUH PENERAPAN STRATEGI ACTIVE LEARNING TIPE GIVING QUESTIONS AND GETTING ANSWER (GQGA) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 BAYANG KABUPATEN PESISIR SELATAN - Indra Welni, Desna; Rismen, Sefna; Rahima, Rahima (Pendidikan Matematika, 2014)
ABSTRACTÂ The background from this research is a low comprehension students mathematic concept at SMPN 2 Bayang. This is caused by system of student learning over memorization so students are easier to forget about the materials provided. This research aims to description the development of math students activity and to know that students math concept comprehension by applying active learning strategies (GQGA) better than students math concept comprehension using conventional teaching class VIII SMPN 2 Bayang. This type of research was experiment. The instrument is acomprehension students mathematics test like essay with reliability test is 0,9186. Data analysis was performed using Minitab test the obtained P-value = 0.026 so the research hypothesis is accepted. so it can be concluded that the students understanding of mathematical concepts that use active learning strategy type (GQGA) better than conventional learning eighth grade students of SMP Negeri 2 Bayang.